2019
DOI: 10.3390/sports7100218
|View full text |Cite
|
Sign up to set email alerts
|

Isometric Posterior Chain Peak Force Recovery Response Following Match-Play in Elite Youth Soccer Players: Associations with Relative Posterior Chain Strength

Abstract: The purpose of this study was to determine changes in two tests of lower limb isometric posterior chain force (IPC-F) following 90 min of match-play in elite youth soccer players and the interaction between relative strength and recovery profile. 14 players (age: 16 ± 2 years) performed 3 × 3 second IPC-F tests unilaterally at 30° and 90° of knee and hip flexion pre- and post-match, +24 h, +48 h, and +72 h post-match. Peak force was recorded for both limbs, combined and expressed relative to bodyweight (N/kg).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
5
19
1
5
Order By: Relevance
“…Our results, indicating deficits of 9.9-15.7% from a relatively large sample identified strength decreases in excess of those regarded as substantial for injury risk (Paul et al, 2014;Wollin et al, 2018) and clearly greater than the typical error associated with the measurement system (6.3%) (Ryan et al, 2019). This in conjunction with previous research, may indicate an increased injury risk during congested fixture periods (Bueno et al, 2021;Carling et al, 2016;Constantine et al, 2019;Wollin et al, 2018), as players may be participating in matches with residual localised fatigue from previous activity (Silva et al, 2018). Figure 2 illustrates that there were inter-individual hip strength differences at all time points, with some participants experiencing more fatigue than others.…”
Section: Isometric Hip Strengthsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results, indicating deficits of 9.9-15.7% from a relatively large sample identified strength decreases in excess of those regarded as substantial for injury risk (Paul et al, 2014;Wollin et al, 2018) and clearly greater than the typical error associated with the measurement system (6.3%) (Ryan et al, 2019). This in conjunction with previous research, may indicate an increased injury risk during congested fixture periods (Bueno et al, 2021;Carling et al, 2016;Constantine et al, 2019;Wollin et al, 2018), as players may be participating in matches with residual localised fatigue from previous activity (Silva et al, 2018). Figure 2 illustrates that there were inter-individual hip strength differences at all time points, with some participants experiencing more fatigue than others.…”
Section: Isometric Hip Strengthsupporting
confidence: 74%
“…dose-response). Previous studies have identified a reduction in eccentric hamstring peak torque or strength of 12-20% after acute soccer activity, which may elevate hamstring injury risk late in matches and the following 48-72hrs (Bueno et al, 2021;Constantine et al, 2019;Huygaerts et al, 2020;Small et al, 2010). However, no studies to our knowledge have explored the combination of isometric hip and eccentric hamstring strength to offer a more complete insight into the lower limbdose-response.…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad, la tecnología ha permitido que el deporte de alto rendimiento estandarice diversos procesos como lo son los de rehabilitación, entrenamiento y readaptación (50,51). Dentro de la readaptación, el deportista debe tener parámetros de calidad de movimiento, fuerza, control neuromuscular, estabilidad que son medidas en el periodo de tiempo entre la rehabilitación de campo y la readaptación deportiva donde entre las principales herramientas utilizadas están: Encoder lineales y rotatorios, Dispositivos isométricos, máquinas de evaluación isocinetica, ergoespirometria, placas de fuerza, Nordbord, Groinbar, electromiografía de superficie, GPS, evaluación biomecánica y test de campo donde estos dispositivos y pruebas arrojan datos cuantitativos que permiten tomar decisiones desde un perfil estadístico y monitorizar el proceso de forma constante permitiendo la identificación de imbalances musculares, índices de relación entre los músculos, niveles de fatiga, consumo máximo de oxígeno en umbrales de rendimiento, activación neuromuscular y su relación con la lesión de forma específica (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). En la figura 5 se establecen las herramientas de monitorización del proceso de readaptación deportiva…”
Section: Fuente De Elaboración Propia 2022unclassified
“…relación entre los músculos, niveles de fatiga, consumo máximo de oxígeno en umbrales de rendimiento, activación neuromuscular y su relación con la lesión de forma específica (52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64). En la figura 5 se establecen las herramientas de monitorización del proceso de readaptación deportiva Figura 5 (Monitorización del proceso de readaptación deportiva) Fuente de elaboración propia 2022 La readaptación de gestos deportivos en campo es uno de los pilares más importantes en el proceso de retorno deportivo donde se deben realizar ejercicios de tipo funcional que estimulen distintos tipos de gestos tales como patrones lineales, patrones laterales, patrones diagonales, frenos, desaceleraciones, aceleraciones, gestos unipodales, gestos bilaterales, estabilidad unipodal, estabilidad ante eventos inesperados, movimientos multidireccionales, estabilidad, equilibrio, salto, toma de decisiones basados en gestos del deporte (15)(16)(17).…”
Section: Título En Españolunclassified
“…Only one study had a high risk of bias, with a score ≤4 (see Table S1). There were 88 observational studies (i.e., 94%), with 82 prospective cohort studies [41,[43][44][45][46][47][48][49]51,52,[54][55][56][59][60][61][86][87][88]90,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][111][112][113][114][116][117][118][119][120][121][122][123]…”
Section: Characteristics Of the Studies And Risk Of Biasmentioning
confidence: 99%